Safety and immunogenicity of a recombinant adenovirus type-5 vector-based Ebola vaccine in healthy adults in Sierra Leone: a single-centre, randomised, double-blind, placebo-controlled, phase 2 trial. Issue 10069 (11th February 2017) - Zhu, Feng-Cai; Wurie, Alie H; Hou, Li-Hua; Liang, Qi; Li, Yu-Hua; Russell, James B W; Wu, Shi-Po; Li, Jing-Xin; Hu, Yue-Mei; Guo, Qiang; Xu, Wen-Bo; Wurie, Abdul R; et al.
Summary: Background: A recombinant adenovirus type-5 vector-based vaccine expressing the glycoprotein of Ebola Zaire Makona variant showed good safety and immunogenicity in a phase 1 trial of healthy Chinese adults. We aimed to assess the safety and immunogenicity of this vaccine in healthy adults in Sierra Leone and to determine the optimal dose. Methods: We did a single-centre, randomised, double-blind, placebo-controlled, phase 2 clinical trial at Sierra Leone–China Friendship Hospital, Freetown, Sierra Leone. We recruited healthy adults aged 18–50 years who were HIV negative, had no history of Ebola virus infection, and had no previous immunisation with other Ebola vaccine candidates. Participants were sequentially enrolled and randomly assigned (2:1:1), by computer-generated block randomisation (block size of eight), to receive the high-dose vaccine (1·6 × 10 11 viral particles), low-dose vaccine (8·0 × 10 10 viral particles), or placebo (containing only vaccine excipients, with no viral particles). Participants, investigators, and study staff (except two study pharmacists) were masked from treatment allocation. The primary safety outcome was occurrence of solicited adverse reactions within 7 days of vaccination, analysed by intention to treat. The primary immunogenicity outcome was glycoprotein-specific antibody responses at days 14, 28, and 168 after vaccination, analysed in all vaccinated participants who had blood samples drawn for antibody tests. The trial is registered with the Pan African Clinical Trials Registry, number PACTR201509001259869, and is completed. Findings: During Oct 10–28, 2015, 500 participants were enrolled and randomly assigned to receive the high-dose vaccine (n=250), low-dose vaccine (n=125), or placebo (n=125). 132 (53%) participants in the high-dose group, 60 (48%) in the low-dose group, and 54 (43%) in the placebo group reported at least one solicited adverse reaction within 7 days of vaccination. Most adverse reactions were mild and self-limiting. Solicited injection-site adverse reactions were significantly more frequent in vaccine recipients (65 [26%] in high-dose group and 31 [25%] in low-dose group) than in those receiving placebo (17 [14%]; p=0·0169). Glycoprotein-specific antibody responses were detected from day 14 onwards (geometric mean titre 1251·0 [95% CI 976·6–1602·5] in low-dose group and 1728·4 [1459·4–2047·0] in high-dose group) and peaked at day 28 (1471·8 [1151·0–1881·8] and 2043·1 [1762·4–2368·4]), but declined quickly in the following months (223·3 [148·2–336·4] and 254·2 [185·0–349·5] at day 168). Geometric mean titres in the placebo group remained around 6·0–6·8 throughout the study period. Three serious adverse events (malaria, gastroenteritis, and one fatal asthma episode) were reported in the high-dose vaccine group, but none was deemed related to the vaccine. Interpretation: The recombinant adenovirus type-5 vector-based Ebola vaccine was safe and highly immunogenic in healthy Sierra Leonean adults, and 8·0 × 10 10 viral particles was the optimal dose. Funding: Chinese Ministry of Science and Technology and the National Health and Family Planning Commission, Beijing Institute of Biotechnology, and Tianjin CanSino Biotechnology.